Three-Month Pulmonary Function and Radiological Outcomes in COVID-19 Survivors: A Longitudinal Patient Cohort Study. (14th November 2020) - Liao, Xuejiao; Wang, Ying; He, Ziyi; Yun, Yongxing; Hu, Ming; Ma, Zhenghua; Huang, Ling; Cai, Qingxian; Xu, Lin; Hao, Yuantao; Liu, Lei
Abstract: Background: This study aimed to investigate pulmonary function and radiological outcomes in a group of coronavirus disease 2019 (COVID-19) survivors. Methods: One hundred seventy-two COVID-19 survivors in a follow-up clinic in a referral hospital underwent high-resolution computed tomography (CT) of the thorax and pulmonary function at 3 months after hospital discharge. Results: The median duration from hospital discharge to radiological and pulmonary function test (interquartile range) was 90 (88–95) days. Abnormal pulmonary function was found in 11 (6.40%) patients, and abnormal small airway function (FEF25-75% ) in 12 (6.98%). Six (3.49%) patients had obstructive ventilation impairment, and 6 (3.49%) had restrictive ventilatory impairment. No significant differences in lung function parameters were observed between the nonsevere and severe groups. Of 142 COVID-19 patients who underwent CT scan, 122 (85.91%) showed residual CT abnormalities and 52 (36.62%) showed chronic and fibrotic changes. The ground-glass opacities absorption in the lungs of severe cases was less satisfactory than that of nonsevere patients. The severe patients had higher CT scores than the nonsevere cases (2.00 vs 0.00; P  < .001) Conclusions: Of the COVID-19 survivors in our study, 6.40% still presented pulmonary function abnormality 3 months after discharge, which did not vary by disease severity during hospitalization; 85.91% of patients had abnormalities on chest CT, with fibrous stripes and ground-glass opacities being the most common patterns.